Estuarine acidification mirrors the ocean trend and correlates with the El Niño Southern Oscillation - Jason S. Grear (Limnology and Oceanography, 2025)
The pH of seawater has direct impacts on marine organisms and is one of several key variables for determining ecosystem‐scale rates of carbon fixation, metabolism, and air–sea exchange. Based on previous estimates from four decades of monitoring data, the global ocean is acidifying at a rate of −0.0017 pH units yr. However, in biologically active coastal environments where such longer‐term pH data sets are limited to low resolution glass electrode measurements, analyses have focused on the shorter‐term biogeochemical details of diurnal and seasonal variation. A better understanding of decade‐scale trends in estuaries is needed and is achievable with available data. Here, Bayesian methods were used to combine previously reported pH trends with a multivariate time series analysis of a 25 year dataset (1996–2020) covering 16 fixed stations in the U.S. National Estuarine Research Reserve system. After temperature normalization, the estimated trend was −0.0013 pH units yr. This estimate is less negative than previously reported but is also more precise, resulting in a 63% probability of a negative trend in unsampled estuaries. Over decadal time scales, biological response calculations predict demographically relevant impacts on early life stage mortality in bivalves and potentially other calcifying marine organisms. Additional multivariate analyses indicated strong association between the El Niño Southern Oscillation and estuarine pH both before and after temperature normalization. Although seasonal decoupling of biological production and respiration was expected to produce stronger pH seasonality at higher latitudes, no such pattern was detected either before or after temperature normalization.

Effect of nutrient reductions on dissolved oxygen and pH: a case study of Narragansett bay - Hongjie Wang; Daniel L. Codiga; Heather Stoffel; Candace Oviatt; Kristin Huizenga; Jason Grear (Frontiers in Marine Science, 2024)
To assess the consequences of nutrient reduction strategies on water quality under climate change, we investigated the long-term dynamics of dissolved oxygen (DO) and pH in Narragansett Bay (NB), a warming urbanized estuary in Rhode Island, where nitrogen loads have declined due to extensive wastewater treatment plant upgrades. We use 15 years (January 2005-December 2019) of measurements from the Narragansett Bay Fixed Site Monitoring network. Nutrient-enhanced phytoplankton growth can increase DO in the upper water column while subsequent respiration can reduce water column DO and enhance bottom water acidification, and vice-versa. We observed significant decreases in surface DO levels, concurrent with a significant increase in bottom DO, associated with the nitrogen load reduction. Surface DO decline was primarily attributed to reduced intensity of primary productivity, supported by a concurrent decrease in surface chlorophyll concentrations. Meanwhile, the influence of reduced organic matter respiration led to the increase of bottom DO levels by 9 µmol kg -1 (approximately 0.2 mg L -1 for typical summer temperature and salinity) over a 15-year period, which overcame the opposite influence of oxygen reduction from solubility decreases due to warming temperatures. In contrast, long-term changes in surface pH have not exhibited discernible trends beyond natural variability, likely due to the complex and sometimes opposing influences of biological activity and changing river flow conditions. We observed a slight increase in bottom pH, associated with the increase in DO in bottom water. Notably, future variations in freshwater discharge, particularly linked to extreme precipitation events, may further influence water carbonate chemistry and thereby impact pH dynamics. This study highlights the necessity of long-term time series measurements in helping understand the impacts of environmental management practices in improving water quality in coastal regions during a changing climate.

Ocean acidification but not nutrient enrichment reduces grazing and alters diet preference in Littorina littorea - Gordon T. Ober; Carol S. Thornber; Jason S. Grear (Marine Biology, 2022)

Community Science for Coastal Acidification Monitoring and Research - Parker Randall Gassett; Katie O’Brien-Clayton; Carolina Bastidas; Jennie E. Rheuban; Christopher, W. Hunt; Elizabeth Turner; Matthew Liebman; Emily Silva; Adam, R. Pimenta; Jason. Grear; Jackie Motyka; Daniel McCorkle; et al. (Coastal Management, 2021)

In situ recovery of bivalve shell characteristics after temporary exposure to elevated p CO 2 - Jason Grear; Adam Pimenta; Harriet Booth; Doranne Borsay Horowitz; Wilson Mendoza; Matthew Liebman (Limnology and Oceanography, 2020)
Ocean uptake of carbon dioxide (CO 2 ) is causing changes in carbonate chemistry that affects calcification in marine organisms. In coastal areas, this CO 2 ‐enriched seawater mixes with waters affected by seasonal degradation of organic material loaded externally from watersheds or produced as a response to nutrient enrichment. As a result, coastal bivalves often experience strong seasonal changes in carbonate chemistry. In some cases, these changes may resemble those experienced by aquacultured bivalves during translocation activities. We mimicked these changes by exposing juvenile hard clams (500 μ m, Mercenaria mercenaria ) to p CO 2 in laboratory upwellers at levels resembling those already reported for northeastern U.S. estuaries (mean upweller p CO 2 = 773, 1274, and 1838 μ atm) and then transplanting to three grow‐out sites along an expected nutrient gradient in Narragansett Bay, Rhode Island (154 bags of 100 clams). Prior to the field grow‐out, clams exposed to elevated p CO 2 exhibited larger shells but lower dry weight per unit volume (dw/V). However, percent increase in dw/V was highest for this group during the 27‐day field grow‐out, suggesting that individuals with low dw/V after the laboratory treatment accelerated accumulation of dw/V when they were transferred to the bay. Treatments also appeared to affect shell mineral structure and condition of digestive diverticula. Although treatment effects diminished during the field grow‐out, clams that were preexposed for several weeks to high p CO 2 would likely have been temporarily vulnerable to predation or other factors that interact with shell integrity. This would be expected to reduce population recovery from short‐term exposures to high p CO 2 .

Carbon Stable Isotope Values in Plankton and Mussels Reflect Changes in Carbonate Chemistry Associated with Nutrient Enhanced Net Production - Autumn Oczkowski; Bryan Taplin; Richard Pruell; Adam Pimenta; Roxanne Johnson; Jason Grear (Frontiers in Marine Science, 2018)

Progress and Challenges in Coupled Hydrodynamic-Ecological Estuarine Modeling - Neil K. Ganju; Mark J. Brush; Brenda Rashleigh; Alfredo L. Aretxabaleta; Pilar del Barrio; Jason S. Grear; Lora A. Harris; Samuel J. Lake; Grant McCardell; James O’Donnell; David K. Ralston; Richard P. Signell; et al. (Estuaries and Coasts, 2016)

Ocean and Coastal Acidification off New England and Nova Scotia - Dwight Gledhill; Meredith White; Joe Salisbury; Helmuth Thomas; Ivy Misna; Matthew Liebman; Bill Mook; Jason Grear; Allison Candelmo; R. Christopher Chambers; Christopher Gobler; Christopher Hunt; et al. (Oceanography, 2015)

An Approach to Predict Risks to Wildlife Populations from Mercury and Other Stressors - Diane Nacci; Marguerite Pelletier; Jim Lake; Rick Bennett; John Nichols; Romona Haebler; Jason Grear; Anne Kuhn; Jane Copeland; Matthew Nicholson; Steven Walters; Wayne R. Munns (Ecotoxicology, 2005)